2016
DOI: 10.1142/s0219519416400157
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Coronary Stent Deployment in Tapered Arteries: Impact of Arterial Tapering

Abstract: Coronary stents are used to prop open blocked arteries in order to restore normal blood flow. A major setback in this technology is in-stent restenosis (ISR), which gravely limits the clinical success of stents, especially in tapered vessels. The present study used the finite element method to study the effects of arterial tapering on the biomechanical behavior of both stents and vessels during stent deployment inside tapered arteries. The effect of arterial tapering was demonstrated by a combination of corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The bile duct with larger β is, prone to cause ISR, and the short axis plane is more likely to be injured than the long axis plane. The value of the maximum von Mises stress in this research is about 0.220 MPa, while that in the vessel wall expanded by a stainless stent is 1 MPa, 6 and that in the vessel wall expanded by a poly-L-lactic acid (PLLA) stent is 3 MPa. 22 Accordingly, the magnesium alloy stent generated smaller concentration stress values in the bile duct wall than other stents, having a low risk level with reference to ISR, fully in agreement with the finding of Lu et al 27 The incomplete stent apposition caused by the gap between the outer surface of the stent and the inner wall of the bile duct may result in stent shifting.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The bile duct with larger β is, prone to cause ISR, and the short axis plane is more likely to be injured than the long axis plane. The value of the maximum von Mises stress in this research is about 0.220 MPa, while that in the vessel wall expanded by a stainless stent is 1 MPa, 6 and that in the vessel wall expanded by a poly-L-lactic acid (PLLA) stent is 3 MPa. 22 Accordingly, the magnesium alloy stent generated smaller concentration stress values in the bile duct wall than other stents, having a low risk level with reference to ISR, fully in agreement with the finding of Lu et al 27 The incomplete stent apposition caused by the gap between the outer surface of the stent and the inner wall of the bile duct may result in stent shifting.…”
Section: Discussionmentioning
confidence: 59%
“…In the process of stent expansion, the stent deformation, as well as the shortening speed and recoil force of the stent, and so on, caused by the extrusion and the shape of lumens 5–7 and diseased tissues, 8,9 has a great influence on the expansion performance of the stent. Of course, the mechanical behavior of the expansion of the stent in different lumens will, in turn, affect the biomechanical environment of the lumen wall in contact with the stent, and may change the geometry of the lumen, and the upper stress of the lumen wall caused by the expansion of the stent plays an important role in the occurrence of restenosis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the effects of the artery tapering level on the structural properties of coronary stent design as well as its biomechanical influence on the blood-vessel during stent deployment were sought [75]. In 2014, McGrath et al [76] investigated the axial buckling which observed through crimping of a long diameter Nitinol stent and through clarification of the buckling mechanism to remove it from the design. However, for investigating whether stent and blood-vessel deformation have a main effect on the hemodynamic environment in stented coronary arteries [77].…”
Section: Fig 3 -Distributions Of Von-mises-stress On (A) Stent Model ...mentioning
confidence: 99%
“…and radiopacity have been enhanced [21], [29], [35], [51], [61], [66]. As well as, the biodegradable stent (BDS) give the possibility to improve long-term patency rates for supporting the artery wall to heal, other researchers examined the mechanical properties for fully covered biodegradable stent by using finite element method (FEM) [16], [27], [33], [43], [56], [76]. Nevertheless, the geometric of stents design response on the mechanical behavior which leads to innovate or develop the new generation of stent geometry, however, stent versus stent researches one kind of randomized trials to show superiority of the new stent designs that should be guarantee fatigue strength and a sufficient vessel scaffolding [3], [4], [15], [39], [50], [55], [71], [74].…”
Section: Motivations Related To Long-term Improvement Of Stent Struct...mentioning
confidence: 99%